Holding the fort: a business case for testing security. Issue 6 (June 2016) - Dixit, Sameer
Abstract : With the cost of breaches sky-rocketing year on year, many of the perimeter security vendors – or firewall companies – that are your organisation's first line of defence are failing and being breached themselves. It's now more important than ever to subject your critical infrastructure to real world threat modelling and penetration testing. This helps identify the security gaps in your network, wireless, mobile and web applications as 80–85% of these tests reveals critical security flaws.